1995
DOI: 10.1159/000168835
|View full text |Cite
|
Sign up to set email alerts
|

Zidovudine Is Beneficial in Human Immunodeficiency Virus Associated Nephropathy

Abstract: Human immunodeficiency virus associated nephropathy (Hivan) is a distinct renal disease described in patients infected with the human immunodeficiency virus (HIV). Hivan is characterized by a nephrotic syndrome, enlarged kidneys, a histologic finding of focal and segmental glomerulosclerosis, and a very rapid progression to end-stage renal disease (ESRD). No therapeutic intervention has been shown, in a prospective evaluation, to either alter the course of established Hivan or to influence the emergence of Hiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 14 publications
1
48
0
Order By: Relevance
“…Ifudu et al (67) studied 23 HIV-1-seropositive patients, 14 of whom had at least 2ϩ proteinuria. HIVAN was diagnosed in the five patients who underwent renal biopsy.…”
Section: Antiretroviralsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ifudu et al (67) studied 23 HIV-1-seropositive patients, 14 of whom had at least 2ϩ proteinuria. HIVAN was diagnosed in the five patients who underwent renal biopsy.…”
Section: Antiretroviralsmentioning
confidence: 99%
“…Patients with HIVAN who are not treated with antiretrovirals, ACE inhibitors, or prednisone, generally have a poor renal prognosis with a mean time to progression to ESRD of 1 to 3 mo (13,67,72). The renal prognosis in the HAART era is less well defined.…”
Section: Prognosismentioning
confidence: 99%
“…Early uncontrolled and largely retrospective studies suggested a beneficial effect of this agent, primarily if treatment was initiated when serum creatinine was normal or slightly elevated. In a prospective study using historical controls, Ifudu et al [24]reported on 23 patients, only 14 of whom had either proteinuria or renal insufficiency, who were treated with AZT for a mean of 20 months. Eight noncompliant patients progressed to ESRD.…”
Section: Treatmentmentioning
confidence: 99%
“…Of the 15 compliant patients, none progressed to ESRD, and none who were initially without proteinuria developed that condition. Half of the 28 historical controls with nephrotic syndrome and ESRD who were never treated with AZT died within 10 months of initiation of hemodialysis [24]. Positive as this study is, it suffers from a lack of tissue diagnosis for most patients; only 5 had a kidney biopsy, but all 5 had HIVAN.…”
Section: Treatmentmentioning
confidence: 99%
“…This is due in part to the development of an HIV-associated nephropathy (HIVAN), characterized by massive proteinuria and rapidly progressive renal failure, in a subset of patients infected with HIV (8,13,24). Although combination antiretroviral therapy appears to slow the progression of HIVAN to end-stage renal disease (ESRD) in many cases (9,16,27), the total number of persons with ESRD due to HIVAN is expected to increase due to the increasing prevalence of HIV-1 infection (E. J. Schwartz, L. Szczech, J. A. Winston, and P. E. Klotman, J.…”
mentioning
confidence: 99%